Reputational Risk Management Strategies for Islamic Banking: Comparison of Bank Victoria Syariah and Bank Syariah Indonesia - Oftafiana, Triya; Subagiyo, Rokhmat; Nur Asiyah, Binti; Fauzan (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Reputation reflects a public perception of banking activities. The existence of reputation risks can affect the performance of the banking industry sector because they can lead to various other risks. In 2023, Bank Victoria Syariah and Bank Syariah Indonesia, as Islamic banking in Indonesia, experienced reputational risk and caused different impacts. Objective: This study aims to determine the reputation risk management strategies of Bank Victoria Syariah and Bank Syariah Indonesia in mitigating, managing, and controlling reputation risk and then compare them. Method: The research approach used is a comparative qualitative approach. The research data was obtained from risk management reports contained in the annual reports of Bank Victoria Syariah and Bank Syariah Indonesia in 2023. Result: The results showed that Bank Victoria Syariah and Bank Syariah Indonesia focus on monitoring risk exposure and handling customer complaints. Bank Victoria Syariah's reputation risk management strategy focuses more on risk mitigation measures and proper risk handling so that the company continues to grow healthy and perform well after the case. While Bank Syariah Indonesia focuses its reputation risk management strategy on mitigation actions and post-disaster reputation recovery (disaster recovery), its implementation has not been maximized, impacting the decline in BRIS shares. Implication: The results of this research are expected to provide an understanding to readers and be used as a material of consideration for financial institutions as a reference material in addressing reputational risks that threaten the main institutions of Sharia Banking